Clinical presentation of pediatric patients with symptomatic SARS-CoV-2 infection during the first months of the COVID-19 pandemic in a single center in Mexico City - Aragón-Nogales, Ranferi; Zurita-Cruz, Jessie; Vázquez-Rosales, Guillermo; Arias-Flores, Rafael; Gómez-González, Claudia; Montaño-Luna, Victoria; Sámano-Aviña, Mariana; Pacheco-Rosas, Daniel; Flores-Ruiz, Eric; Villasís-Keever, Miguel; Miranda-Novales, Guadalupe (Frontiers in Pediatrics, 2022)
Background: The clinical spectrum COVID-19 is broad, from asymptomatic to severe cases and death. The objective of this study is to compare the clinical presentation of patients attended during the first months of the SARS-CoV-2 pandemic in a third-level pediatric hospital. Methods. Design: prospective cohort study. Patients with viral respiratory disease or suspected case of COVID-19, evaluated at the Pediatric Hospital, National Medical Center XXI Century, Mexico City, from March 21, 2020, to January 13, 2021. Statistical analysis: Chi-square test and exact Fisher test were used for comparisons; a logistic regression model was constructed to identify clinical, or laboratory characteristics associated to critical disease. A p value < 0.05 was considered statistically significant. Results: 697 patients met the operational definition of viral respiratory disease or suspected case of COVID-19 and underwent rRT-PCR SARS-CoV-2 testing. Patients with a positive result were included: of 181 patients (26%), 121 (66.8%) had mild disease and were treated as outpatients, 60 (33.1%) were hospitalized. Six patients met criteria for multisystem inflammatory syndrome in children (MIS-C). Of the 60 inpatients, 65% were male, and 82% had one or more comorbidities. Main comorbidities were cancer (42%) and overweight (15%). Median hospital stay was nine days. Inpatients had a higher frequency of fever, general malaise, dyspnea, chills, polypnea and cyanosis, than outpatients (p < 0.05). Only 21.4% of the outpatients had one or more comorbidities, which was lower than in hospitalized patients (p < 0.001). Laboratory data at admission were similar between critically ill and those with moderate and severe disease. Patients who developed pneumonia were at higher risk of critical disease, while older age was associated to a better prognosis. Thirteen of the 60 inpatients died (mortality 7.1%). All but one had one or more comorbidities: four had cancer, four congenital heart disease, one chronic kidney disease and epilepsy, one Epstein-Barr Virus-Induced Hemophagocytic Lymphohistiocytosis, one obesity and one Diabetes Mellitus. Conclusion: Hospital mortality is high, especially in children with comorbidities. Despite two years have passed since the beginning of the COVID-19 pandemic, the epidemiological and clinical data on children are still helpful to improve their prognosis